Glycochenodeoxycholate-induced lethal hepatocellular injury in rat hepatocytes. Role of ATP depletion and cytosolic free calcium. - Spivey, J R (1993)
Chenodeoxycholate is toxic to hepatocytes, and accumulation of chenodeoxycholate in the liver during cholestasis may potentiate hepatocellular injury. However, the mechanism of hepatocellular injury by chenodeoxycholate remains obscure. Our aim was to determine the mechanism of cytotoxicity by chenodeoxycholate in rat hepatocytes. At a concentration of 250 microM, glycochenodeoxycholate was more toxic than either chenodeoxycholate or taurochenodeoxycholate. Cellular ATP was 86% depleted within 30 min after addition of glycochenodeoxycholate. Fructose, a glycolytic substrate, maintained ATP concentrations at 50% of the initial value and protected against glycochenodeoxycholate cytotoxicity. ATP depletion in the absence of a glycolytic substrate suggested impairment of mitochondrial function. Indeed, glycochenodeoxycholate inhibited state 3 respiration in digitonin-permeabilized cells in a dose-dependent manner. After ATP depletion, a sustained rise in cytosolic free calcium (Cai2+) was observed. Removal of extracellular Ca2+ abolished the rise in Cai2+, decreased cellular proteolysis, and protected against cell killing by glycochenodeoxycholate. The results suggest that glycochenodeoxycholate cytotoxicity results from ATP depletion followed by a subsequent rise in Cai2+. The rise in Cai2+ leads to an increase in calcium-dependent degradative proteolysis and, ultimately, cell death. We conclude that glycochenodeoxycholate causes a bioenergetic form of lethal cell injury dependent on ATP depletion analogous to the lethal cell injury of anoxia.